ANALYSIS OF CONSUMER BEHAVIOR TOWARDS DECISION TO PURCHASE Tahu AT UD MAKMUR ETERNAL - nury (Journal Knowledge Industrial Engineering (JKIE), 2023)
Consumer behavior can be said to be something unique,because the tastes and attitudes towards each person's object are different. In addition, consumers come from several segments, so what is desired and needed is also different. The benefits gained from this study are to provide information on how much influence purchasing decisions have on consumer behavior and consumer behavior.The method of collection in research uses observation, interview, dissemination of questionnaires, and documentation. The number of samples of 30 respondents obtained using accidental sampling.The test results showed that the total consumer behavior ofthe end showed with a total distribution of taste and texturevariables (X1) of 0.464 or 46.4% of product display variables (X2) of -0.077 or -77% variable accessibility level (X3) of 0.481 or 48.1% variable price (X4) of 0.051 or 51% of service and hospitality level variables (X5) of 0.051 or 51% against consumer behavior variables (Y) with final total results shown by a determination or test coefficient (R) of 0.659 or 65.9% and sisnya was influenced by another research test (F) of 45,810. The number of variable contributions that are dominant variables affecting consumer behavior is the accessibility level variable (X3) of 0.481 or 48.1%.